Why Is the Electronic Health Record So Challenging for Research and Clinical Care? - Holmes, John H.; Beinlich, James; Boland, Mary R.; Bowles, Kathryn H.; Chen, Yong; Cook, Tessa S.; Demiris, George; Draugelis, Michael; Fluharty, Laura; Gabriel, Peter E.; Grundmeier, Robert; Hanson, C. William; Herman, Daniel S.; Himes, Blanca E.; Hubbard, Rebecca A.; Kahn, Charles E., Jr.; Kim, Dokyoon; Koppel, Ross; Long, Qi; Mirkovic, Nebojsa; Morris, Jeffrey S.; Mowery, Danielle L.; Ritchie, Marylyn D.; Urbanowicz, Ryan; Moore, Jason H. (Methods of Information in Medicine, 2021)
Background The electronic health record (EHR) has become increasingly ubiquitous. At the same time, health professionals have been turning to this resource for access to data that is needed for the delivery of health care and for clinical research. There is little doubt that the EHR has made both of these functions easier than earlier days when we relied on paper-based clinical records. Coupled with modern database and data warehouse systems, high-speed networks, and the ability to share clinical data with others are large number of challenges that arguably limit the optimal use of the EHRObjectives Our goal was to provide an exhaustive reference for those who use the EHR in clinical and research contexts, but also for health information systems professionals as they design, implement, and maintain EHR systems.Methods This study includes a panel of 24 biomedical informatics researchers, information technology professionals, and clinicians, all of whom have extensive experience in design, implementation, and maintenance of EHR systems, or in using the EHR as clinicians or researchers. All members of the panel are affiliated with Penn Medicine at the University of Pennsylvania and have experience with a variety of different EHR platforms and systems and how they have evolved over time.Results Each of the authors has shared their knowledge and experience in using the EHR in a suite of 20 short essays, each representing a specific challenge and classified according to a functional hierarchy of interlocking facets such as usability and usefulness, data quality, standards, governance, data integration, clinical care, and clinical research.Conclusion We provide here a set of perspectives on the challenges posed by the EHR to clinical and research users.
Keywords: electronic health records; user-computer interface; standards; medical informatics; systems integration